Unintended Consequences? The Changing Composition of Immigration to the UK after Brexit - Jonathan Portes (Institute of Labor Economics (IZA), 2024)
The end of free movement and the introduction of the post-Brexit migration system represent the most important changes to the UK migration system in half a century. Coinciding with the aftereffects of the pandemic, the result has been very large changes both to the numbers of those coming for work and study, and to their composition, both in terms of countries of origin and in the sectors and occupations of new migrants. It has also resulted in a political backlash, resulting in significant further changes to the system announced in December 2023. I discuss the evidence to date of the impact of recent migration trends on the UK economy and labour market, distinguishing between different sectors.
Keywords: F22; J48; J61; J68; 330; migration; productivity; labour markets; Brexit